In Search of "Industrial Harmony": The Process of Labour Law Reform in Manitoba, 1984 - Black, Errol (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper examines the roots of the controversy over industrial relations within Manitoba NDP, looks at the process which the government initiated as a means of delivering its commitments to organized labour and outlines the conditions by which the business class in Manitoba forced the government to retreat.